PROSPECTS FOR REGIONAL TAX MANAGEMENT DEVELOPMENT IN THE IMPLEMENTATION OF TAX POLICY OF UKRAINE - Kurnosov O.V. (Pressing Problems of Public Administration, 2016)
In the article the preconditions of transition from bureaucratic paradigm of manager to the existing contradictions tax governance in the region are analyzed. Strategic goals, tactical objectives, principles, functions, methods, trends, institutions, regional tax management, assessment of the effectiveness of its implementation are considered. Development the concept of a regional tax management in Ukraine is proposed.